Activities, Resources, and Learning Environment: A Case Study of Science Learning at Sekolah Alam - Nova Andriani; Maison; Nazarudin (Postgraduate, University of Mataram, 2025)
This study examines science education activities, resources, and the learning environment at Sekolah Alam Al Fath Jambi Junior High School. Using a case study approach, the research involves direct observations, interviews with teachers and students, and learning materials analysis to understand the impact of various learning methods on student outcomes. The findings highlight that science learning activities align with the Sekolah Alam concept, emphasizing project-based, experiential, nature-based, and collaborative approaches. Learning occurs inside and outside the classroom, utilizing the natural surroundings for exploration and field experiments. Resources include school gardens, outbound areas, natural materials, and collaborations with local experts. The learning environment, assessed through the WIHIC questionnaire, supports student success through dimensions like cohesiveness, teacher support, involvement, task orientation, cooperation, equity, enjoyment, and academic efficacy. This study underscores the effectiveness of nature-integrated and experiential approaches in enhancing science learning outcomes and offers recommendations for advancing educational practices in similar settings.